The application of Cooperative Learning Model Type of Teams Games Tournament to Enhance students' learning results in Indonesian Language at Elementary School Students - Wilma Sil Wahyuli; Ayunis Ayunis; Rica Azwar (The Future of Education Journal, 2024)
Learning Indonesian at State Elementary School 01 Ulak Karang Selatan, previously students were less active because the learning model used by the teacher was less creative, making students bored in learning. Therefore, this research applies the Teams Games Tournament Type Cooperative Learning Model. This research aims to see improvements in student learning outcomes. This research is useful for teachers and schools to improve Indonesian language learning outcomes. The type of research in this research is classroom action. Data collection techniques are: observation, tests and documentation. The results of the research show that the initial condition is that the students' pre-cycle Indonesian language learning results have an average score of 51 with a completion percentage of 11% in the poor category. In cycle I, students' Indonesian language learning results obtained an average score of 78 with a percentage of 74% in the sufficient category. In cycle II, students' Indonesian language learning results obtained an average score of 85 with a percentage of 89% in the very good category. Thus, it can be concluded that using the Cooperative Teams Games Tournament model can improve Indonesian language learning outcomes for class II students at State Elementary School 01 Ulak Karang Selatan